2015
DOI: 10.1016/j.sdentj.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Oral conditions in renal disorders and treatment considerations – A review for pediatric dentist

Abstract: This article reviews the current understanding of the oral and dental aspects of chronic renal disease (CRD). A PubMed literature search was performed and all relevant studies were assessed. As the number of people suffering from CRD increases worldwide, dentists are expected to encounter more patients with CRD who need oral care. In children, CRD can elicit a wide spectrum of oral manifestations in the hard and soft tissues. Bleeding, altered drug metabolism, impaired immune function, and an increased risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 31 publications
2
64
0
10
Order By: Relevance
“…Between them, noticeably, bone changes are prominent and refer to renal osteodystrophy (16). Approximately, 90% of CKD cases are involved in jaw bone changes (10). Bone anomalies in CKD patients reflect the defect in metabolism of calcium which results in secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between them, noticeably, bone changes are prominent and refer to renal osteodystrophy (16). Approximately, 90% of CKD cases are involved in jaw bone changes (10). Bone anomalies in CKD patients reflect the defect in metabolism of calcium which results in secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients should be reminded of earlier dental treatment and the importance of good oral hygiene habits (30). Owing to oral complications, these patients require to visit a dentist before and after transplantation (10). Dental panoramic radiographs have a long history of radiological exam in dentistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…intake, side effects of medications (primarily antihypertensive drugs), possible disruption of the salivary glands, and secondary oral breathing problems due to lung perfusion 12,15,28 . However, decreased salivary flow was not observed in studies conducted in post-dialysis patients when compared to healthy subjects because once the procedure is over water balance is normal levels 7 .…”
Section: Hernández Cmentioning
confidence: 99%
“…g) Tartar: Patients with CRF are susceptible to develop dental calculus due to increased levels of urea in saliva, phosphorus and large amounts of calcium carbonate that some patients take as part of their treatment 6,9,15 . A study conducted in 180 patients in Iran showed a 100% prevalence of oral abnormalities, being the most common: tartar, high DMF and plaque indexes and gingivorrhagia 34 .…”
Section: Hernández Cmentioning
confidence: 99%